The Impact of the Cross Fit Program for 12 Weeks on the Maximum Oxygen Consumption and Some Body Components Among Students in the Military Sports Training Department at AL –istiqlal University for Security Sciences/Palestine - Dabeek, Qasem Assad; Zakarnih, Ismael Ahmad; Jomhoor, Haifaa Abdallah; Benabderrahman, Abderraouf (Advances in Social Sciences Research Journal, 2023)
The research aims to investigate the impact of a 12-week Cross Fit program on the maximum oxygen consumption and some physiological components of the body among students of the Military Sports Training Department at University of AL-istiqlal for Security Sciences. The researchers utilized an experimental approach to achieve optimal results, focusing on the quality of the training program to understand its physiological effects on maximum oxygen consumption, various body components, and the performance of the students. The study examined the impact of two different training programs from The cross-fit program.The first program was applied on the experimental group, while the regular training program was implemented for the control group. The sample consisted of 40 military students from the Military Sports Training Department at AL-istiqlal University. They were purposively selected from the study population and were in good health The sample individuals were randomly assigned to two groups: control (20) and experimental (20). They were evaluated through measurements and physiological tests before and after a 12-week period of military training. The training program for the experimental group, known as Cross Fit, demonstrated a significant impact and improvement on maximum oxygen consumption and some body components "Where the improvement rate reached the maximum oxygen consumption (38.8%) milliliters/kg/min, the improvement rate on the body mass index (-9.95%) kg/m², and the improvement rate on muscle mass (9.67%) kg. The improvement rate on metabolic rate during rest for students was (5.55%) kcal/day. The experimental group showed a favorable outcome in the dimensional measurement. Researchers recommend the incorporation of diverse cross-fit exercises into daily military programs at AL-istiqlal University due to their numerous benefits on vital body functions and components."